Antioxidant and hepatoprotective potential of Plantago major growing in Egypt and its major phenylethanoid glycoside, acteoside. Issue 5 (3rd August 2018) - Eldesoky, Ahmed H.; Abdel‐Rahman, Rehab F.; Ahmed, Osama K.; Soliman, Gamal A.; Saeedan, Abdulaziz S.; Elzorba, Hisham Y.; Elansary, Amira A.; Hattori, Massao
Abstract: The defatted aqueous methanolic extract of the air‐dried aerial parts of Plantago major, collected from Nile delta, Egypt, was evaluated for its antioxidant and hepatoprotective effects. The major phenolic constituent; acteoside was isolated. Meanwhile, P. major exhibited potent hepatoprotective effect as it inhibited the serum activity elevation of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and gamma‐glutamyl transferase (GGT) enzymes and total and direct bilirubin. It increased the serum total protein and albumin and attenuated CCl4 ‐induced lipid peroxidation (LPO) and increased GSH in the liver homogenates. Liver histopathology supported the biochemical findings. Acteoside inhibited lipopolysaccharide induced production of nitric oxide in RAW264.7 macrophages (IC50, 75.0 μM) and scavenged both superoxide radical (IC50, 1.51 μM) and DPPH radical (IC50 of 11.27 µM). P. major showed significant DPPH scavenging activity in vitro (IC50, 7.32 μg/mL). It could be concluded that, P. major has potent antioxidant, anti‐inflammatory, and hepatoprotective activities. Practical applications: Plantago major L. is an edible plant that is used as food, particularly at the end of spring, just before the harvest of common vegetables. The plant grows wildly at canal banks of the Nile delta in Egypt and represents a very cheap food for farmers when frequent vegetables are not available. The research showed that the defatted aqueous methanolic extract has potential antioxidant and hepatoprotective effects in rats. The effect was very similar to the commercially used drug silymarin; indicating that it could be used as very cheap healthy food, food supplement or neutraceutical preparation to provide liver support for patients suffering from hepatic dysfunction. The main constituent acteoside was isolated and exhibited potent antioxidant and anti‐inflammatory activities in vitro, besides being safe on primary rat hepatocytes. Therefore this project provides a very cheap hepatoprotective drug for liver support, and a source of safe antioxidant and anti‐inflammatory compound.